2001
DOI: 10.1046/j.1365-2869.2001.00226.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep complaints and risk factors for excessive daytime sleepiness in adult males in Northern Ireland

Abstract: The prevalence of sleep complaints in Northern Ireland is unknown. Sleep disruption can result in excessive daytime sleepiness (EDS), with significant socioeconomic consequences. The aim of this study was to assess the prevalence of sleep complaints and to determine risk factors for EDS in a Northern Irish community. From an urban and rural community of 499 111 people, a random sample of 3391 adult men were sent a questionnaire by mail. Questions were asked regarding sleep, EDS and medical history. There were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 22 publications
(24 reference statements)
3
32
1
1
Order By: Relevance
“…12 The slight female preponderance in respondents (58%) probably reflects the composition of the targeted population (58% female), but it was similar to that (58%) reported in a study of health factors, sampling 9897 adults over the age of 65. 13 We are thus confident of sampling in a similar manner to larger studies, and that we can make some meaningful comparisons to other published reports.…”
Section: Discussionsupporting
confidence: 74%
“…12 The slight female preponderance in respondents (58%) probably reflects the composition of the targeted population (58% female), but it was similar to that (58%) reported in a study of health factors, sampling 9897 adults over the age of 65. 13 We are thus confident of sampling in a similar manner to larger studies, and that we can make some meaningful comparisons to other published reports.…”
Section: Discussionsupporting
confidence: 74%
“…A number of previous studies have examined the relationship between excessive daytime sleepiness and various types of sleep problems and underlying diseases. 5,[7][8][9][10][11][12] A British study reported that symptoms of insomnia such as difficulty initiating sleep and difficulty maintaining sleep, breathing pauses or leg pain during sleep, and depressive disorder were associated with excessive daytime sleepiness. 9 In Japan, Liu et al reported that excessive daytime sleepiness was associated with short sleep duration, insomnia symptoms, subjective sleep insufficiency and use of sleep-enhancing medication.…”
Section: Methodsmentioning
confidence: 99%
“…The specific 'while driving' situation was adopted for the question, as this had often been used in other epidemiologic surveys of excessive daytime sleepiness. 10,15 Various subjective and objective methods have been suggested for measuring excessive daytime sleepiness, but one of the most clinically useful methods is the Epworth Sleepiness Scale. 15 This measures the probability of falling asleep in eight different situations.…”
Section: Logistic Regression Analysis Of Excessive Daytime Sleepinessmentioning
confidence: 99%
“…On the basis of this classification system, three major types of insomnia have been observed: (1) sleep onset insomnia (difficulty in falling asleep); (2) sleep maintenance insomnia (interrupted sleep characterized by frequent nighttime awakenings); and (3) terminal insomnia (early-morning awakenings coupled with an inability to return to sleep). These may occur singly or in combination [10][11][12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%